2016
DOI: 10.1002/mop.29674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taper parameters on free spectral range of non‐adiabatic tapered optical fibers for sensing applications

Abstract: We investigated the effects of taper parameters on the free spectral range of transmission spectrum of non-adiabatic tapers. From experimental results, the optimum profile for the tapered fiber in terms of taper angle, waist diameter, and length are 11.500 mrad, 10 lm, and 20 mm, respectively. V C 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:798-803, 2016; View this article online at wileyonlinelibrary.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…So the tapered fiber can be used as a filter to generate stable multiple wavelengths [40]- [42]. Further study showed that the free spectral range (FSR) can be expressed as [43], [44]:…”
Section: Discussionmentioning
confidence: 99%
“…So the tapered fiber can be used as a filter to generate stable multiple wavelengths [40]- [42]. Further study showed that the free spectral range (FSR) can be expressed as [43], [44]:…”
Section: Discussionmentioning
confidence: 99%
“…Its real-time control system allows manipulation of dimensions, uniformity, and reproducibility of the fabricated taper as the pulling speed and heat are kept at a constant value of 1 mm/s and 42 W, respectively. Figure 1 illustrates the geometry of the non-adiabatic tapered optical fiber used throughout the experiment, with parameters of waist diameter, waist length, up-taper length and down-taper length set at 10 µm, 12 mm, 5 mm and 5 mm following previously reported work (Musa et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A simpler alternative proposed in recent times is the tapered optical fibers. Tunability in tapered fibers is acquired through its high sensitivity towards environmental changes such as stress, strain, and temperature (Da Silveira et al, 2015;Ali et al, 2014;Musa et al, 2016). The stretching of the fiber down to tens of micrometres makes it more pliable which enables bending at a much larger angle without physical damage.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed sensing system consist of two tapers region that are separated with various distances of 1, 2, and 3 cm. When light is transmitted into the first taper area, the core mode is excited to high-order mode in the cladding area and propagated along the cladding [20]. The guided high-order mode that penetrates into the cladding layer produces a strong evanescent field between the cladding surface and the external environment [21].…”
Section: Dt Pof Principlementioning
confidence: 99%
“…One can see that the tapered structure, both single and double tapered induced the modal interference phenomenon as indicated by the appearance of peaks. The interference spectrum only appear when the tapered structure in non-adiabatic condition [20]. In non-adiabatic conditions, the core mode will be excited to the higher order mode due to the geometry of the tapered structure in down-taper transition [20].…”
Section: Experimental Set-upmentioning
confidence: 99%